2016
DOI: 10.1038/ncomms12610
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective single-site Earth-abundant metal catalysts at metal–organic framework nodes

Abstract: Earth-abundant metal catalysts are critically needed for sustainable chemical synthesis. Here we report a simple, cheap and effective strategy of producing novel earth-abundant metal catalysts at metal–organic framework (MOF) nodes for broad-scope organic transformations. The straightforward metalation of MOF secondary building units (SBUs) with cobalt and iron salts affords highly active and reusable single-site solid catalysts for a range of organic reactions, including chemoselective borylation, silylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
238
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(245 citation statements)
references
References 55 publications
4
238
0
3
Order By: Relevance
“…Theq uality of the extracted reflection intensities can be increased by coupling ADT with precession electron diffraction (PED). [36][37][38][39][40] Arylboronic acids are very important intermediates in organic synthesis that can be used in ap lethora of synthetic procedures. [34,35] This is especially relevant in the rich domain of C À Ha ctivation catalysis,w ith formation of for example,C ÀC, CÀN, or CÀBb onds.…”
mentioning
confidence: 99%
“…Theq uality of the extracted reflection intensities can be increased by coupling ADT with precession electron diffraction (PED). [36][37][38][39][40] Arylboronic acids are very important intermediates in organic synthesis that can be used in ap lethora of synthetic procedures. [34,35] This is especially relevant in the rich domain of C À Ha ctivation catalysis,w ith formation of for example,C ÀC, CÀN, or CÀBb onds.…”
mentioning
confidence: 99%
“…10-12 ,. 4,5,6 Further, the ν CO values IR spectra similarly provideinge essential details of the local environments of metal sites on solid surfaces. 713 The typical mononuclear metal carbonyl complex on a metal oxide support is heterogeneous, characterized by a smear of species and broad ν CO bands, but Miessner et al 8 14 showed that mononuclear rhodium carbonyls bonded to dealuminated HY zeolite are characterized by narrow ν CO bands, indicating that the zeolite bonding sites are almost all the same.…”
mentioning
confidence: 99%
“…As an example, in 2016, Lin and co‐workers reported the post‐synthetic metalation of Zr 6 (μ 3 ‐O) 4 (μ 3 ‐OH) 4 ‐nodes in UiO‐68 by soaking the material in solutions of Co 2+ and Fe 2+ salts. It was suggested, according to X‐ray absorption spectroscopy, that the added metals bind to the (μ 3 ‐OH) bridge found on the surface of the SBU (Figure ) . The introduction of site isolated, coordinatively deficient Lewis acids in the MOF pore, transformed the MOF into a highly active, reusable catalysts, which has demonstrated utility in a variety of site‐selective sp 3 C‐H functionalization, including benzylic C−H borylation, silylation and amination reactions.…”
Section: Functionalizing Mofs For Organic Transformationsmentioning
confidence: 99%
“… (A) Metalation of the SBUs of UiO‐68 with CoCl 2 . (B) An electron‐deficient Co II center located in a sterically protected environment at the SBU of UiO‐68 will favor the activation of less‐hindered alkyl C−H bonds . Copyright 2016 Springer Nature.…”
Section: Functionalizing Mofs For Organic Transformationsmentioning
confidence: 99%